Applying Personal Inquiry to Strengthen Thinking and Research Skills an ATL in Upper IB-PYP - Olbytri, Fitria; Nenotek, Kalysa; Regina Caeli, Patricia; Agustina Amelia, Maria (Perspektif Ilmu Pendidikan, 2025)
This study aims to examine the implementation of Personal Inquiry as a reflective learning approach to enhance Thinking Skills and Research Skills as part of the Approaches to Learning (ATL) framework within the International Baccalaureate Primary Years Programme (IB-PYP) curriculum. The research is motivated by the challenges of 21st-century learning, which require that elementary school students develop higher-order thinking skills and independent research abilities. A descriptive qualitative method was conducted over seven weeks at an international school in Bekasi, involving students from grades 4, 5, and 6. Data were collected through classroom observations, student project documentation, and reflective journals, and analyzed using Miles and Huberman’s interactive model. The findings revealed that the six stages of Personal Inquiry; Identify, Inquire, Investigate, Innovate, Improve, and Reflection. Effectively encouraged conceptual and analytical thinking, as well as learning autonomy. Students were able to formulate reflective questions, evaluate credible information sources, and communicate their findings through creative products such as PowerPoint presentations with themes including Microplastics, Fungus, and Dance. The process also strengthened students’ metacognitive awareness and learner agency, aligning with the IB Learner Profile attributes of being reflective and knowledgeable. The study concludes that Personal Inquiry serves as an effective framework for integrating research with critical thinking. Future research is recommended to explore the implementation of this model within Indonesia’s Kurikulum Merdeka and its potential to cultivate other IB learner attributes such as communicator and principled learner.